Design, implementation, and evaluation of a new journaling file system with data and meta-data separation - Piernas Cánovas, Juan (2005)
This thesis describes the design, implementation and evaluation of a journaling file system called DualFS. Our main goal is to improve disk I/O by designing a new file system which must have two features: a better performance than that of current file systems, and a fast consistency recovery after a system crash.